Accurate and Robust Displacement Measurement for FMCW Radar Vibration Monitoring - Xiong, Yuyong; Peng, Zhike; Xing, Guanpei; Zhang, Wenming; Meng, Guang (IEEE sensors journal, 2018)
Non-contact displacement measurement based on the phase-based microwave interferometry technology has attracted growing interest in recent years. In this paper, aiming to exploit the frequency-modulated continuous wave (FMCW) radar-based vibration monitoring technique, the principle and detailed procedure for extracting the displacement time series of vibration movement are illustrated. The approximate maximum likelihood approach is proposed to extract the phase history of beat signals across multiple sweep periods. Moreover, the measurement accuracy of vibration displacement extraction and several practical issues of this technique are evaluated and concerned. Both simulated and experimental validations are provided to show the effectiveness and robustness of the proposed method and approach.